1969
DOI: 10.1113/jphysiol.1969.sp008830
|View full text |Cite
|
Sign up to set email alerts
|

The response of motor neurones to intramuscular injection of botulinum toxin

Abstract: SUMMARY1. The dry mass and nucleic acid content of both nerve cell bodies and their nucleoli were measured by interference microscopy and ultra-violet absorption microspectrography respectively: succinoxidase and acetylcholine hydrolase activities were also determined. Autoradiography was used to follow synthesis of deoxyribonucleic acid (DNA) by glial cells, and to follow nucleic acid and protein metabolism in muscle fibres.2. After injection of botulinum toxin the synthesis of ribosomal RNA by the neurone fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 62 publications
1
44
0
Order By: Relevance
“…Rats were killed 90 min after injecting uridine and 60 min after leucine: previous unpublished studies had indicated that these intervals were optimum for detecting the altered uptake and incorporation which accompanied altered nucleolar nucleic acid content and dry mass. The autoradiographic techniques have been described previously (Watson, 1965;Sumner & Watson, 1972 (Watson, 1966b) Unlike such measurements in isolated neuronal nuclei (Watson, 1968(Watson, , 1969(Watson, , 1970, the nucleolar dry mass and nucleic acid content of neuroglial cells had to be measured within the total isolated cell, including thin covering and underlying layers of perinuclear cytoplasm in addition to nucleoplasin. Initial studies indicated that the values obtained for nucleolar dry mass and nucleic acid content were over-estimated by 18 and by 12 % respectively: similar values were obtained in cells reacting after axotomy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rats were killed 90 min after injecting uridine and 60 min after leucine: previous unpublished studies had indicated that these intervals were optimum for detecting the altered uptake and incorporation which accompanied altered nucleolar nucleic acid content and dry mass. The autoradiographic techniques have been described previously (Watson, 1965;Sumner & Watson, 1972 (Watson, 1966b) Unlike such measurements in isolated neuronal nuclei (Watson, 1968(Watson, , 1969(Watson, , 1970, the nucleolar dry mass and nucleic acid content of neuroglial cells had to be measured within the total isolated cell, including thin covering and underlying layers of perinuclear cytoplasm in addition to nucleoplasin. Initial studies indicated that the values obtained for nucleolar dry mass and nucleic acid content were over-estimated by 18 and by 12 % respectively: similar values were obtained in cells reacting after axotomy.…”
Section: Methodsmentioning
confidence: 99%
“…Study of groups two and four allowed the significance of metabolic change in the nerve cell, which occurred under these circumstances (Watson, 1970) to be distinguished from the significance of retraction and re-expansion of the dendritic tree, which was already retracted following the previous axotomv, and underwent no re-expansion until the axon reinnervated denervated muscle (Summer & Watson, 1971). In the fifth group 250 pg botulinum toxin type D was injected into the extrinsic and intrinsic muscles of the left half of the tongue (Watson, 1969) to impede neuromuscular transmission without loss of axoplasm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example is axotomy itself, in which premature return to the cell body of material normally transported along the axon in an anterograde direction could, in principle, trigger the effects of axotomy (Grafstein, 1983). Another example is intramuscularly injected botulinum toxin (botox), which can evoke axotomy-like changes in motoneurons after 2-3 weeks (Watson, 1969;Pinter et al, 1991) but exerts its primary action presynaptically, in which it inhibits acetylcholine (ACh) release (Molgo et al, 1990;Meunier et al, 2002).…”
Section: Introductionmentioning
confidence: 99%